Ultrasonic Doppler MTI system for evaluation of aortocoronary bypass graft patency - NOWICKI, A.; REID, J. M.; SPENCER, M. P. (Archives of Acoustics, 1984)
A new version of an analog multi-channel serial processing imaging gated pulse Doppler (IGPD) was developed. By combining double I/Q fixed echo cancellers with a phase detector and a double-loop recirculating delay line integrator (all made from C.C.D. delay lines), we obtained the degree of cancellation better than 60 dB. The penetration range of the device was 12 cm permitting the investigation of the intracardiac flow. The results of the preliminary application of IGPD to the detection of patency of coronary bypass grafts will be shown.